Pengadilan Tata Usaha Negara - Najwa Ashwarina; Harlan Hidayah; Farhan Azka; Ahmad Maulid (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
PTUN was officially regulated through Law Number 5 of 1986. This law establishes the PTUN as a judicial institution that has the authority to resolve administrative disputes between citizens and the government. With the establishment of the PTUN, the public now has a legal forum to sue decisions that are considered detrimental, which is expected to increase public trust in the government and provide protection for individual rights. Over time, the PTUN has undergone various reforms to improve the quality and efficiency of services. Law Number 9 of 2004 is one of the important steps in strengthening the role of the PTUN, with the aim of accelerating the dispute resolution process. This reform aims to create a system that is more responsive to the needs of the community and ensures that every citizen can access justice more easily